Climate Risk and Bank Profitability in the MENA Region: The Moderating Role of Financial Development - Khemiri, Mohamed Ali (International Journal of Energy Economics and Policy, 2025)
This study pursues three key objectives: first, to examine the impact of climate risk on bank profitability, measured by return on assets (ROA) and return on equity (ROE); second, to assess the role of financial development (FD) in influencing bank profitability; and third, to determine whether financial development moderates the relationship between climate risk and bank profitability. Using a sample of 68 conventional banks in the MENA region (2005-2020) and employing the SGMM methodology, we split the MENA region in two sub-regions. The first block contains the Gulf Cooperation Council (GCC) countries with a sample of 33 banks and, the second covers the non-GCC countries with a sample of 35 banks. Results reveal that climate risk reduces bank profitability, while financial development enhances it. Additionally, financial development mitigates the negative effect of climate risk on profitability. However, sub-sample results differ: for GCC banks, FD shows a positive impact, climate risk a negative one, and their interaction a positive effect, whereas for non-GCC banks, climate risk and its interaction with FD are insignificant.